Prevalence and Antibiotic Resistance of Gram-Negative Pathogenic Bacteria Species Isolated from Periplaneta americana and Blattella germanica in Varanasi, India. - D Leshan Wannigama; Rishabh Dwivedi; Alireza Zahraei-Ramazani (Tehran University of Medical Sciences, 2014)
Background: Cockroaches are among the medically important pests found within the human habitations that cause serious public health problems. They may harbor a number of pathogenic bacteria on the external surface with anti- biotic resistance. Hence, they are regarded as major microbial vectors. This study investigates the prevalence and antibiotic resistance of Gram-negative pathogenic bacteria species isolated from Periplaneta americana and Blattella germanica in Varanasi, India. Methods: Totally, 203 adult cockroaches were collected form 44 households and 52 food-handling establishments by trapping. Bacteriological examination of external surfaces of Pe. americana and Bl. germanica were carried out using standard method and antibiotics susceptibility profiles of the isolates were determined using Kirby-Bauer disc diffusion methods. Results: Among the places, we found that 54% had cockroache infestation in households and 77% in food- handling establishments. There was no significant different between the overall bacteria load of the external surface in Pe. americana  (64.04%)  and  Bl.  germanica  (35.96%).  However  the  predominant  bacteria  on  cockroaches  were Klebsiella pneumonia, Escherichia coli,  Enterobacter aerogenes, and  Pseudomonas aeruginosa. However, Kl. pneumoniae and Ps. aeruginosa were the most prevalent, drug-resistant strains were isolated from the cockroaches with 100% resistance to sulfamethoxazole/ trimethoprim and ampicillin. For individual strains of bacteria, Escherichia coli was found to have multi-resistance to four antibiotic tested, Citrobacter freundii four, Enterobacter aerogenes and Proteus mirabilis to three. Conclusion: Cockroaches are uniformly distributed in domestic environment, which can be a possible vector for transmission of drug-resistant bacteria and food-borne diseases.